Development of Augmented Reality Technology Integrated Learning Media on the Topic of Chemistry and Matter - Liza, Wira Rahma; Guspatni, Guspatni (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Augmented Reality (AR) technology allows interaction between the real world and objects in the virtual world in a three-dimensional form. With these advantages, AR will be a learning media that can increase students' enthusiasm for learning chemistry, especially on abstract chemistry concepts, and require the right learning media to visualize them. This type of research is Educational Design Research with the Plomp development model. The subjects of this study are UNP chemistry lecturers, chemistry teachers, and students at three senior high schools in Sumatera Barat. The object of this study is an augmented reality integrated learning media. The research instruments used were a needs analysis questionnaire, a validity test questionnaire, and a practicality test questionnaire. The data analysis technique uses the Aiken'V formula. The study results show that the developed learning media is included in the valid and practical categories with the validity values of content, construction, and quality respectively being 0.87; 0,85; and 0.85. Meanwhile, teachers' and students' average practicality score index results were 0.97 and 0.92. Thus, the learning media integrated with augmented reality technology in the chemistry concept for the E phase of SMA/MA chemistry has been successfully developed, validated, and practically used in learning.